The utility of pharmacogenetic testing to support the treatment of bipolar disorder - Ielmini M; Poloni N; Caselli I; Espadaler J; Tuson M; Grecchi A; Callegari C (Pharmacogenomics and Personalized Medicine, 2018)
Marta Ielmini,1 Nicola Poloni,1 Ivano Caselli,1 Jordi Espadaler,2 Miquel Tuson,2 Alessandro Grecchi,3 Camilla Callegari1 1Department of Medicine and Surgery, Division of Psychiatry, University of Insubria, Varese, Italy; 2AB-BIOTICS S.A, R&D Unit, Sant Cugat del Valles, Barcelona, Spain; 3ASST Santi Paolo e Carlo Borromeo, Division of Psychiatry, Milan, Italy Background: Bipolar disorder (BD) is a frequent cause of disability, health care costs, and risk of suicide. Pharmacogenetic tests (PGTs) could help clinicians to identify those patients predisposed to the occurrence of adverse events (AEs) improving the understanding of the correlation between genetic variants and drug response.Materials and methods: The study evaluated 30 patients affected by BD type I or II (according to Diagnostic and Statistical Manual of Mental Disorders, version 5) who underwent the PGT Neurofarmagen® (AB-BIOTICS SA, Barcelona, Spain) between March 2016 and March 2017. The primary aim of this study was to identify if the treatment prescribed by the psychiatrists was consistent with the treatment suggested by the PGT at T0 (corresponding to the test report communication). As a secondary aim, we wanted to assess if clinicians had changed the treatment (in case of discordance) at T1 (3-month follow-up visit) according to the results of the PGT.Results: At T0, only 4 patients (13%) had an optimal therapy in line with the PGT suggestions. At 3-month follow-up, 13 patients (40%) had received a change of therapy consistent to the test, showing a significant statistical improvement in the Clinical Global Impression item Severity (CGI-S) score over time compared to those not having changes consistent with the test. Regarding AEs, at baseline 9 out of 10 (90%) of the patients who received a therapy modification according to the test presented AEs, and a significant within-group reduction was observed after 3 months (p = 0.031).Conclusion: Despite the small sample size, the study shows promising data about the usefulness of PGT to support clinicians in reaching a more effective and tolerated treatment in the routine approach of BD. Keywords: pharmacogenetics testing, bipolar disorder, personalized medicine, pharmacogenetics, adverse events, tolerability, mood disorder